Client Security Price Reactions to the Laventhol and Horwath Bankruptcy - Baber, William R.; Kumar, Krishna R.; Verghese, Thomas (Journal of Accounting Research, 1995)
Auditing, Bankruptcy, Market reaction, Audit quality